Benchmarking academics through sustainable assessment criteria: an Indian case study. Issue 3 (7th April 2015) - Singh, Bikram Jit; Joshi, Rakesh
Abstract : Purpose: – The purpose of this paper is to primarily emphasize on improvement of student's academic excellence through devising and implementing a competent Internal Assessment Criteria that indirectly improves their results and passing rates in exams. Design/methodology/approach: – In present system, Internal Assessment Criteria has evolved as critical factor having lot of margin for bringing improvement in student's academics by redesigning or editing the existing one, appropriately. Assessment criteria are re-optimized by strategic implementation of well proved Six Sigma's DMAIC approach. Findings: – It is a one of rarely seen effort to transform Assessment Criteria by identifying the statistical relations between internal marks and external marks secured by students in an end semester university exams. The proposed framework and its validation through an Indian case study, ignites the application of this structured Six Sigma approach in higher education for necessary excellence. Research limitations/implications: – The whole work revolves around the Indian engineering environments, moreover the case has been restricted and elaborate facts for only unaided (private) engineering universities. Practical implications: – The paper can be utilized to stimulate thinking about the fine tuning of Assessment Criteria through proven Six Sigma methodology in current Indian academic settings and further safeguarding the interests of managements, students and society, simultaneously. Originality/value: – The formulation of upcoming challenges before Indian engineering system are outcome of intense literature survey. Focussing on always neglected "Assessment Criteria" and its re-optimization by statistical approach of Six Sigma is hard to found and has immense scope in future for reaching at desired academic hikes.